El elemento fantástico en la obra el perfume de Patrick Suskind - Carrion Gutierrez, Katherine Elizabeth (2016)
The research work entitled “The fantastic element in the novel The Perfume” by Patrick Suskind has as general objective to analyze and identify the author’s literary fantasy in the mentioned work. To develop this analysis, scientific methods were used, such as, descriptive, analytic-synthetic, inductive-deductive and the hermeneutical method as the specific method of analysis which allowed to know and make value judgments of the fantastic element in the literature of Suskind. As main result this research has detected the loss of imagination in our historic reality by the incorporation of technology, the use of social networks and low literacy. We can say first that the author perfectly sets his novel in the eighteenth century in specific places in France. Secondly we can conclude the presence of Grenuille and his amazing olfactory power. Finally we can talk Suskind mechanism to convert the historical reality of the novel in Real fantastic. That’s why it´s concluded that fantasy has been immersed in our society since ancient times until today and it plays an important role in men individual nature allowing us to go beyond the limits and standards of reality. So the readers are advised to get out the common and sometimes routine life, and let themselves be wrapped in this genre allowing them to open their minds to new ideals.